Vernacularization of The Interpretation of The Qur’an Al-Karim by The Ulama Tiga Serangkai (Abdul Halim Hasan, Abdurrahim al-Haitami, and Zainul Arifin Abbas) - Dedi Masri; Randy Putra Alamsyah; Muhammad Azizan Sabjan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study examines aspects of vernacularisation in tafsir al-Quran al-Karim by Ulama Tiga Serangkai. Various values of locality and culture in the interpretation of the Quran cannot be separated from the interpretation of the mufassir. This is a literature research with the primary source of tafsir al-Quran al-Karim by Ulama Tiga Serangkai. This research uses descriptive analysis and the conceptual theory of vernacularisation. The results show that vernacularisation is not only a process of language exchange from Arabic to local languages, but also includes locality elements. Tafsir al-Quran al-Karim has two types of vernacularisation: diction and narrative or content of interpretation. The form of vernacularisation in tafsir al-Quran al-Karim uses the word Lembu (cow) to explain the meaning of baqarah, Pertukangan (Work) is used to define a job done by every human being. In the form of narrative or content of interpretation tafsir al-Quran al-Karim tells a hikayat at the beginning of each letter, hikayat in the Malay tradition is literature that is closely related to the daily life of the community. As in QS. Ali Imran Tiga Serangkai scholars began by explaining the saga of the Germans about the eternal Arabic language.